Leucine and resistance training improve hyperglycemia, white adipose tissue loss, and inflammatory parameters in an experimental model of type 1 diabetes. Issue 1 (March 2018) - Ribeiro, Henrique Quintas Teixeira; Coqueiro, Audrey Yule; Lima, Vanessa Batista de Sousa; Martins, Carlos Eduardo Carvalho; Tirapegui, Julio
Background: Loss of white adipose tissue (WAT), associated with type 1 diabetes (DM1), contributes to increased chronic systemic inflammation. Aim: The aim of this study was to investigate the effects of leucine supplementation and resistance training (RT) in attenuating WAT loss and improving inflammatory parameters and glucose metabolism in DM1 rats. Methods: Thirty-two male Wistar rats were distributed into four groups: DA (sedentary and supplemented with non-essential amino acids (NEAA)), DL (sedentary and supplemented with leucine), DTA (submitted to RT and supplemented with NEAA) and DTL (submitted to RT and supplemented with leucine). DM1 was induced by streptozotocin (STZ). An 8-week period of RT consisted of climbing a ladder with a progressively increased load, and supplementation was offered in the feed. Results: Glycemia, polyphagia and polydipsia were lower in DL, DTA and DTL groups compared with the DA group by approximately 20% ( p <.0001), 28% ( p =.004) and 64% ( p <.0001), respectively. Weight of total WAT and retroperitoneal adipose tissue (RPAT) were higher by approximately 21% ( p =.01) and 54% ( p =.0004), respectively, in DL, DTA and DTL groups compared with DA. However, gene expression of adiponectin and leptin in RPAT was only increased by RT (DTA and DTL) compared with DA and DL by approximately 93% ( p <.0001) and 78% ( p =.0002), respectively. Similarly, the levels of adiponectin in the serum, tissue IL-10 (RPAT) and serum IL-10 were only increased in DTA and DTL compared with DA and DL by approximately 31% ( p =.03), 45% ( p =.0009) and 35% ( p =.003), respectively. Conclusions: Both interventions, isolated or together, reduced hyperglycemia and excessive loss of WAT, but RT was the main factor responsible for attenuating inflammation.